Pengelolaan Pengunjung di Kawasan Wisata Alam Lolai Kabupaten Toraja Utara - Rahayu, Mia; Pratama, Yudha Sakti (Sekolah Vokasi, Universitas Gadjah Mada, 2022)
Pong Torra’ is one of natural tourism attraction in Lolai Natural Tourism Area of North Toraja Regency, that is an expansion of Tana Toraja Regency, according the local regulation of Toraja Utara no. 7 in 2016. This district is focused on being developed as a tourism destination. A high level of tourist visits even reaches 1,000 visitors / day during the high seasons, tourism activities are increasing, while the limited space in the tourist area causes the density of visitors to the tourist area, which will continue to have a negative impact on both the visitor side and also the tourist attraction alone. In addition, according to the Decree of the Minister of Forestry of the Republic of Indonesia No.SK 434 / Menhut-II / 2009, Pong Torra 'is included in the Protected Forest Area of South Sulawesi Province. Therefore, it is necessary to implement visitor management. Qualitative research methods are used to obtain data, through observation, interviews and questionnaire collection. In the visitor profile, it is done by looking at geographical, demographic and psychographic aspects, where from the visitor profile it is known that the dominant visitors traveling in Pong Torra 'are middle-aged / adult visitors, male gender and low of money spending and domestic tourist visits are the highest. In this study, a combination of hard (hard) and soft (soft) approaches was carried out. Through the hard approach, the researcher uses the tourism carrying capacity calculation, which results in a PCC value of 25 visitors / day and an RCC value of 30 visitors / day, from which this value indicates the number of tourist visits that have exceeded the visitor capacity threshold. Meanwhile, a soft approach is carried out by directing and educating visitors through information dissemination and interpretation. The two approaches to managing visitors are carried out using their respective techniques.